'Still may these Attic Glories Reign': How Eighteenth-Century Whig Taste was Shaped by a Political Metaphor. Issue 1 (April 2022) - Brunton, Anna
Abstract : According to the cultural historian Peter Burke, cultural history concentrates on the 'symbolic element in all human activities'. Building on Burke's remark, this essay examines how a particular set of metaphorical ideas shaped new approaches to material and visual culture in the eighteenth-century. The analysis applies a methodologically innovative approach, that of conceptual metaphor theory. This approach is generally used to analyse the hidden ideology found in contemporary political discourse, which finds that the use of similar metaphors by an 'in' group not only reinforces their own ideology, but also serves to create a sense of the 'other', or outsider, and so embodies a power imbalance. The results of my analysis suggest that Whig writers used the metaphor of ancient Greece to create an exclusionary discourse, defined against what they saw as negative values held by an oppositional 'other', in this case Catholic Europe. Whig writers mapped the metaphor of ancient Greece on to their interpretation of political liberty, and this same linguistic patterning shaped concepts of visual and material taste within Whig culture.